Gene cassette knock-in in mammalian cells and zygotes by enhanced MMEJ. (December 2016) - Aida, Tomomi; Nakade, Shota; Sakuma, Tetsushi; Izu, Yayoi; Oishi, Ayu; Mochida, Keiji; Ishikubo, Harumi; Usami, Takako; Aizawa, Hidenori; Yamamoto, Takashi; Tanaka, Kohichi
Abstract Background Although CRISPR/Cas enables one-step gene cassette knock-in, assembling targeting vectors containing long homology arms is a laborious process for high-throughput knock-in. We recently developed the CRISPR/Cas-based precise integration into the target chromosome (PITCh) system for a gene cassette knock-in without long homology arms mediated by microhomology-mediated end-joining. Results Here, we identifiedexonuclease 1 (Exo1 ) as an enhancer for PITCh in human cells. By combining theExo1 and PITCh-directed donor vectors, we achieved convenient one-step knock-in of gene cassettes and floxed allele both in human cells and mouse zygotes. Conclusions Our results provide a technical platform for high-throughput knock-in.